2014
DOI: 10.1002/hipo.22283
|View full text |Cite
|
Sign up to set email alerts
|

Impairments in experience-dependent scaling and stability of hippocampal place fields limit spatial learning in a mouse model of Alzheimer's disease

Abstract: Impaired spatial memory characterizes many mouse models for Alzheimer's disease, but we understand little about how this trait arises. Here we use a transgenic model of amyloidosis to examine the relationship between behavioral performance in tests of spatial navigation and the function of hippocampal place cells. We find that APP mice require considerably more training than controls to reach the same level of performance in a water maze task, and recall the trained location less well 24 hours later. At a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
36
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 48 publications
9
36
1
Order By: Relevance
“…Decreased stability was observed for both place field locations and firing rates. These results are consistent with prior studies that tested place field stability over consecutive laps (Cheng and Ji, ; Ciupek et al, ; Booth et al, ) or sessions (Zhao et al, ) in other AD mouse models. In the latter study, the authors also used a Morris water maze (MWM) task to assess spatial memory at the behavioral level and found that APP Swe/Ind mice were deficient in spatial memory recall.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Decreased stability was observed for both place field locations and firing rates. These results are consistent with prior studies that tested place field stability over consecutive laps (Cheng and Ji, ; Ciupek et al, ; Booth et al, ) or sessions (Zhao et al, ) in other AD mouse models. In the latter study, the authors also used a Morris water maze (MWM) task to assess spatial memory at the behavioral level and found that APP Swe/Ind mice were deficient in spatial memory recall.…”
Section: Discussionsupporting
confidence: 92%
“…Here, we examined place cell representations of space and rhythmic coordination of place cells in the 3xTg mouse model of AD. These mice showed impairments in the stability of place cell maps and reductions in place cell firing rates that were consistent with a number of other rodent models of AD that overexpress disease-related tau and/or APP mutations (Cheng and Ji, 2013;Witton et al, 2014;Zhao et al, 2014;Ciupek et al, 2015;Booth et al, 2016). We also found that rhythmic coordination of place cell spiking by theta and slow gamma rhythms, but not fast gamma rhythms, was disrupted in freely behaving 3xTg mice.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Place cell goal‐coding deficits were reported in a mouse model where reduced DISC1 protein expression leads to a dopamine system disturbance, providing further evidence for dopaminergic involvement (Hayashi, Sawa, & Hikida, ). Interestingly, impaired space‐related place cell dynamics have also been observed in CMI models not based on DISC1 manipulations (Wolff & Bilkey, ; Zaremba et al, ) and amyloidosis‐based Alzheimer's disease models (Mably, Gereke, Jones, & Colgin, ; Zhao, Fowler, Chiang, Ji, & Jankowsky, ). Our study therefore supports previous CMI research involving place cell coding deficits.…”
Section: Discussionmentioning
confidence: 99%
“…An early indication of Alzheimer's is memory impairment, including the loss of spatial memory. A recent study by Zhao et al (2014) From the beginning of his scientific studies O'Keefe has been interested in the brain and behavior. He has focused his research on the limbic system and medial temporal lobe, specifically the amygdala and hippocampus.…”
Section: The Sciencementioning
confidence: 99%